Modelagem matemática aplicada para o corte de carga em uma microrrede ilhada considerando indicadores de qualidade de serviço - Roesler, Pedro Henrique (2021)
In order to improve the reliability of electric energy distribution service, the distributed generation can be used by energy distribution companies to attend groups of consumers demand in a fault moment. However, it is necessary to exist a delimitation of benefited consumers, control and protection equipment, and an operation policy aligned to system’s purposes. In this context, this master’s dissertation proposes an optimization model to improve the use of allocated resources in an energy distribution company microgrid. The mathematical model encompasses the utilization cost of energy storage resources, the possibility of consumers load shedding, and the Brazilian quality indicators of power distribution service. The proposed model is developed in Mixed Integer Linear Programming (MILP) and it is applied to determine the lowest microgrid operational cost, considering load shedding. The optimization model is embedded into a rolling horizon strategy. The proposed solution is applied to an island microgrid with lithium-ion batteries, photovoltaic generators, and controllable loads. The microgrid configuration and the used data are based on a real system. Three experiments are conducted in order to evidence the solution approach capability to provide adequate decisions, even with changes in the systems conditions (demand and available energy). A scalability test is also conducted in order to verify the computational load to obtain solutions in a case with a higher number of involved consumers. The obtained results evidence that the proposed approach is able to define adequate load shedding strategies, which are influenced by the assignment of weighting values in the objective function. The scalability test results, on the other hand, show that more modeling efforts are needed to make the solution scalable as the consumer groups considered increase.